Analysis of Health Promotion Strategies on Knowledge and Attitude of Healthy Lifestyle for Academics and Staff in STIKES ARRAHMA Mandiri Indonesia - Abd Syakur; Katmini Katmini; Ratna Wardani (STIKES Rumah Sakit Anwar Medika, 2022)
The goal of encouraging Clean and Healthy Living Behaviour (PHBS which stands for Perilaku Hidup Bersih & Sehat) in the workplace is to provide employees the tools they need to adopt healthier lifestyles on the job and to encourage them to take an active role in fostering a positive work environment. This research set out to compare the effectiveness of two health promotion approaches (the one-way method and the two-way method) in improving STIKES Arrahma Mandiri Indonesia's faculty members and staff with, and commitment to, implementing PHBS. Preliminary experimental studies of this sort employ a post-test-pre-test design with a single experimental group. Men and women of varying educational and economic backgrounds made up the 70-participant sample used in this study. (p <0.05) Knowledge and attitudes were found to increase significantly with education (p=0.000) and income (p=0.001), but not with age (p=0.324); there was a significant difference (p 0.05) between the control group and the intervention group in both the one-way and two-way methods; the increase in knowledge in the One-Way Method intervention group was 49.75% while in the Two-Way Method intervention group, it was 51.04%; and there was a significant difference (p <0.05). We might generalize from this research that STIKES Arrahma Mandiri Indonesia faculty and staff members’ knowledge and attitudes concerning PHBS are influenced by both individual characteristics and variations in health promotion tactics